Necessity of Empirical Research for Adapting CEFR Proficiency Levels to Burmese as a Foreign Language - San Yu Wai Maung (Southeast Asian Language and Literature Studies, 2026)
The Common European Framework of Reference for Languages (CEFR) has become one of the most influential frameworks in second and foreign language learning, teaching, and assessment since its publication in 2001. While originally developed for European languages, its proficiency descriptors have been widely adopted and adapted across diverse linguistic contexts worldwide. However, in the field of Burmese as a foreign language, the absence of standardized proficiency benchmarks and reference levels continues to create challenges for curriculum design, instructional planning, learner progression, and assessment practices. Consequently, key questions concerning what should be learned at different stages and how language proficiency should be defined remain insufficiently addressed. This study investigates the potential application of the CEFR to Burmese language education through a qualitative descriptive research design. The study draws on document analysis of CEFR policy documents, proficiency descriptors, and existing literature on Burmese language teaching and assessment. Data were analyzed through comparative and contextual analysis to identify opportunities and challenges in adapting CEFR principles to the specific linguistic and sociocultural characteristics of Burmese. The findings indicate that the CEFR provides a valuable reference framework for structuring Burmese language learning outcomes, establishing proficiency benchmarks, and supporting the development of more systematic assessment practices. However, direct adoption of CEFR descriptors is insufficient because several linguistic features of Burmese, including its script, sociolinguistic conventions, and communicative practices, require contextual adaptation. The study therefore argues for a localized CEFR-informed framework that integrates international standards with the specific needs of Burmese language learners. Theoretically, this study contributes to ongoing discussions regarding the transferability and adaptation of global language proficiency frameworks to less commonly taught languages. Practically, the findings offer recommendations for curriculum development, proficiency assessment, and future research on CEFR adaptation in Burmese language education and other underrepresented language contexts.